Ergonomics study of musculoskeletal disorders in an assembly plant / Mohd Rizal Abd Razak and Clement Joseph - Abd Razak, Mohd Rizal; Joseph, Clement (2000)
One of the main objectives of the project is to determine and evaluate the level of ergonomics awareness in our industries. Therefore, the project had been carried out at one of the leading automotive assembler in January 2000. As the workers are the main subjects in this project, the checklist and the questionnaires were used as the tools in order to get the valuable data for us to do an analysis. By using statistical technique for social science or SPSS software for window, we can get the relationship between the dependents and independent variables consist in the questionnaires. The early chapter in this project is the introduction of the musculoskeletal disorders and the workplace factors that contribute to the musculoskeletal disorders. Then we will explain about the processes for assembly of the bus chassis before we commence with the methodologies and analysis for this project.